A Study of the Influence of Fragmentation in Ore-Pass Hang-up Phenomena - Tang,X; Paluszny,A; Zimmerman,RW (American Rock Mechanics Association, 2013)
Abstract: Fragmentation strongly influences the interlocking hang-up phenomena, a common occurrence in conjunction with cohesive arching around draw points in block caving systems. This work presents a brief numerical study of the influence of fragmentation on interlocking hang-up phenomena. Fragment interaction and breakup are simulated numerically by combining the impulse-based energy tracking method (ETM) and the finite element method (FEM) in three dimensions. Numerical tests with varying size of ore fragments are carried out. The breakage of rock fragments is modeled during the entire simulation and the influence of fragmentation is investigated in terms of productivity and the efficiency of draw point extraction. Simulation results with fragmentation are compared to non-fragmentation numerical tests. It is observed that with fragmentation, 1.93% and 2.57% more volume of ore fragments are extracted before hang-up when the initial diameter of ore fragments is 5.775 m and 7.5 m, respectively.